2019
DOI: 10.1136/acupmed-2017-011559
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for pain relief in labour inhibits spinal p38 MAPK-mediated prostaglandin E2 release and uterine prostaglandin E2 receptor expression in rats

Abstract: Background: p38 mitogen-activated protein kinase (p38 MAPK) activation involves the release of prostaglandin E2 (PGE2) and hyperalgesia. We have previously reported that electroacupuncture (EA) relieves labour pain, but the potential mechanisms remain unclear. Objective: To observe the effects of EA on labour pain intensity, serum PGE2 levels and the p38 MAPK signalling pathway in rats during labour. Methods: Female rats copulated with male rats to induce pregnancy, and then received castor oil to trigger labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Evidence suggests PGE2 is a mediator of the inflammatory pain response, 23 and EA has been shown to decrease pain behaviors and PGE2 in various rat models of pain. 24,25 However, there was no difference in levels of serum PGE2 between EA-treated and control guinea pigs. In previous studies, tissues for PGE2 analysis were collected within 1 day of EA treatment, compared to 2 weeks after treatment in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Evidence suggests PGE2 is a mediator of the inflammatory pain response, 23 and EA has been shown to decrease pain behaviors and PGE2 in various rat models of pain. 24,25 However, there was no difference in levels of serum PGE2 between EA-treated and control guinea pigs. In previous studies, tissues for PGE2 analysis were collected within 1 day of EA treatment, compared to 2 weeks after treatment in this study.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, we found that the carrot juice with carotenoids compounds group had lower labor pain after an 8-week intervention compared to the control group. In addition, a previous study found that carotenoids had a strong inhibitory effect on prostaglandin ( 25 ); in fact, prostaglandin has an impact on the pain experienced during labor ( 26 , 27 ). Carotenoids was significantly correlated with pain and antidepressant in Rats with fibromyalgia models ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 This indicates that the p38 MAPK signalling pathway in the spinal dorsal horn mediates pain occurrence. 12,23,24 TNF-α is an important inflammatory cytokine and a downstream molecule of the p38 MAPK pathway that is released in the early stages of nerve injury and the neuroinflammatory process. 25,26,32 Increased TNF-α expression in the spinal dorsal horn has been reported in the formalin-induced pain model.…”
Section: Discussionmentioning
confidence: 99%